2023
DOI: 10.1111/1442-1984.12441
|View full text |Cite
|
Sign up to set email alerts
|

The allelochemical potential of an invasive ornamental plant, the Indian blanket flower (Gaillardia pulchella Foug.)

Krisztina Napsugár Nagy,
Luca Viktória Kardos,
Zsófia Orbán
et al.

Abstract: Global spread of invasive plant species threatens biodiversity significantly, with a particularly high presence of invasives in the Asteraceae family. This is partly due to their wide use as ornamental plants and their rapid reproduction and allelopathy. The Indian blanket flower (Gaillardia pulchella) is a native North American species widely used as an ornamental plant and has become invasive in other countries. Although it contains bioactive compounds, its allelopathic impact on other plants has been largel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 28 publications
1
1
0
Order By: Relevance
“…A 40% water extract concentration of Gaillardia pulchella can inhibit the germination of Brassica napus. Different concentrations of water extracts of G. pulchella inhibited the growth of B. napus roots but promoted the elongation of shoots [38]. This is similar to the results of this study using corn straw water extract treatments.…”
Section: Allelopathic Effects Of Straw Water Extract On Weedssupporting
confidence: 89%
“…A 40% water extract concentration of Gaillardia pulchella can inhibit the germination of Brassica napus. Different concentrations of water extracts of G. pulchella inhibited the growth of B. napus roots but promoted the elongation of shoots [38]. This is similar to the results of this study using corn straw water extract treatments.…”
Section: Allelopathic Effects Of Straw Water Extract On Weedssupporting
confidence: 89%
“…This theory is supported by the results of Kazinczi et al [67], who investigated the allelopathy of several invasive plant species in potted experiments under greenhouse conditions and found stimulating effects in some species, which facilitated the development of cultivated plants, which indicates, on the one hand, the buffering capacity of the soil, and, on the other hand, that each species has a different allelopathic effect. Nagy et al [68], for instance, demonstrated that the allelopathy of the Indian blanket flower (Gaillardia pulchella Foug.) exerts distinct effects on the development of the test plants.…”
Section: Discussionmentioning
confidence: 99%